Teachers’ Beliefs in Integrating Digital Literacy in EFL Classroom: Decomposed Theory of Planned Behavior Perspectives - Hening Laksani; Endang Fauziati; Agus Wijayanto (Indonesian Journal of EFL and Linguistics, 2020)
The need for integrating digital technology into learning instructions has been acknowledge as a most prominent aspect in 21st Century learning. With emerging technology rising in prevalence, a digital consciousness to select and manage digital resources safely, appropriately, and efficiently for digital learning instruction is crucial. This present study is intended to explore teachers’ beliefs in the integration of digital literacy in EFL classroom using Decomposed Theory of Planned Behavior (DTPB) perspectives. The study was a qualitative study by means of case study research design to obtain a reliable understanding of the phenomenon. The data were collected using semi-structured interview, open-ended survey, and documentation. The data were retrieved from the purposively chosen informants based on the familiarity with digital technology. The results indicate relatively high levels of integration and consistent beliefs about the advantages, support from the environment, and the technology availability to integrate digital literacy into teaching learning activities. Recommendations are suggested to advance schools equipment to mediate the better support in constructing technology-enhanced classroom for teachers.